Comparative Genomic Analysis of the 2016 Vibrio cholerae Outbreak in South Korea - Ha, Sung-min; Chalita, Mauricio; Yang, Seung-Jo; Yoon, Seok-Hwan; Cho, Kyeunghee; Seong, Won Keun; Hong, Sahyun; Kim, Junyoung; Kwak, Hyo-Sun; Chun, Jongsik (Frontiers in Public Health, 2019)
In August 2016, South Korea experienced a cholera outbreak that caused acute watery diarrhea in three patients. This outbreak was the first time in 15 years that an outbreak was not linked to an overseas source. To identify the cause and to study the epidemiological implications of this outbreak, we sequenced the whole genome of Vibrio cholerae isolates; three from each patient and one from a seawater sample. Herein we present comparative genomic data which reveals that the genome sequences of these four isolates are very similar. Interestingly, these isolates form a monophyletic clade with V. cholerae strains that caused an outbreak in the Philippines in 2011. The V. cholerae strains responsible for the Korean and Philippines outbreaks have almost identical genomes in which two unique genomic islands are shared, and they both lack SXT elements. Furthermore, we confirm that seawater is the likely source of this outbreak, which suggests the necessity for future routine surveillance of South Korea's seashore.